The “Equal-Opportunity Jerk” Defense: Rudeness Can Obfuscate Gender Bias - Belmi, Peter; Jun, Sora; Adams, Gabrielle S. (Psychological Science, 2022)
To address sexism, people must first recognize it. In this research, we identified a barrier that makes sexism hard to recognize: rudeness toward men. We found that observers judge a sexist perpetrator as less sexist if he is rude toward men. This occurs because rudeness toward men creates the illusion of gender blindness. We documented this phenomenon in five preregistered studies consisting of online adult participants and adult students from professional schools (total N = 4,663). These attributions are problematic because sexism and rudeness are not mutually exclusive. Men who hold sexist beliefs about women can be—and often are—rude toward other men. These attributions also discourage observers from holding perpetrators accountable for gender bias. Thus, rudeness toward men gives sexist perpetrators plausible deniability. It protects them and prevents the first perceptual step necessary to address sexism.